Realization of 25-GHz spaced Ultra densed Spectrum-Sliced WDM PON with 3- spectrum sliced channels using 50-GHz AWGs - Manandhar, Dipen; Shrestha, Surendra (Journal of Lumbini Engineering College, 2023)
We used three spectrum sliced even and odd channels using a pair of 50-GHz Arrayed-waveguide gratings (AWGs) demonstrating the possibility of 25-GHz spaced ultra densed spectrum-sliced wavelength-division[1]multiplexed passive optical network. Those AWGs have an offset of 25 GHz with respect to each other. For the demultiplexing of the channels, we used a pair of 50-GHz AWGs. We intended to use these AWGs as it gives better bit-error rate performances and has two times larger channel bandwidth than conventional 25-GHz AWGs . Moreover, the increased spectral overlap between adjacent channels produces relatively small crosstalk since the channels are incoherent and the irintensity noise is absorbed by the reflective semiconductor amplifiers. The 25-GHz spaced spectrum-sliced spectrum-sliced WDM passive optical network can be realized more easily using 50-GHz AWGs since 50-GHz AWGs are more available in the market than 25- GHz AWGs.